MODELING AS METHOD OF EDUCATIONAL REALITY ABSTRACTION - Borysenko, Iryna; Baliasnikova, Tetiana; Ihnatovych, Tetiana (Studies in Comparative Education, 2018)
The article presents modeling as a research method in current science, the advantages and possibilities of modeling techniques relating to curriculum develop-ment. The opportunity of models to reveal the structure and characteristics and behavior of real object is also carried out. The aim of the article is to analyze modelling and its opportunities in the research process; to characterize models, which go to make up curriculum planning; and the interrelation of curriculum models basic elements. Some approaches to curriculum development proposed by educators are described as well. The article covers the views of Ukrainian educators on the opportunities of modeling in the area of structuring; reflectionofobjectives. It is noted that modeling is used in science in a number of use, in education in particular, as a method of defining new facts about the real object, which is studied. The paper provides an overview of the curriculum development process presented by some European scientists. It is defined that the purpose of curriculum modeling is to provide a structure for examining its key components, which go to make up curricu-lum planning and how these components work. Special attention has been paid to curriculum models by R. Tyler, D. Wheeler, J. Kerr and E. Wragg who considered principle components of models of curriculum development (aims, subject matter, learning experience, evaluation) in their interact-tion. Wragg’s model is characterized as a new look to many-sided nature of curricu-lum. The three dimensions of the model are subject; cross-curricular themes and issues; and set of teaching and learning strategies and methods. It should best ressed that with the help of the model, the process of content structuring can be observed on the basis of three didactic principles of learning: continuity, sequence, knowledge integration. Examples of curriculum models are used to illustrate the procedures in terms of curriculum structuring. It is revealed that the primary content modeling is considered as theoretical reflection of the process of selection, structuring, passing and evaluating of the level of its assimilation by pupils according to the objectives defined.